Konstruksi Citra Aktivisme Mahasiswa di Media Lokal Kalimantan Selatan - Muhammad Nizar Hidayat; Muhammad Najeri Al-Syahrin; Bambang Dwi Waluyo (Jurnal Ranah Komunikasi, 2025)
This study aims to examine the construction of student imagery in local media coverage in South Kalimantan during the 2019–2024 period. The primary focus is directed at how students are represented in the context of demonstrations through online media jejakrekam.com and langkar.id. A total of 157 articles were analyzed using instruments based on three main dimensions: Language/Tone, Content Focus, and Content Visibility. This study uses a quantitative-descriptive approach combined with qualitative reading, and is analyzed using the theoretical framework of Agenda Setting, Framing, Social Construction of Reality, and Communication Influence. The results show that both media do not construct the image of students as moral actors or symbols of change as is common in the historical narrative of the Indonesian student movement. The representation of students is mostly neutral and administrative, without strong symbolic content. The media tend to convey the reasons for the demonstrations informatively, but do not highlight the narrative of the impact or sustainability of the student struggle. Although the demonstrations are routinely covered and accompanied by multimedia elements, the distribution of content on social media is relatively low. These findings indicate a tendency towards depoliticization of narratives about students in local media, which has resulted in a weakening of the symbolic and political construction of students in the contemporary public sphere.